Clinical Presentation, Surgical Treatment, and Outcome in Radial Polydactyly - Dijkman, R. R.; van Nieuwenhoven, C. A.; Hovius, S. E. R.; Hülsemann, W. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2016)
Radial polydactyly or ‘thumb duplication’ is the most common congenital upper limb anomaly (‘CULA’) affecting the thumb. The clinical presentation is highly diverse, ranging from an extra thumb floating on a skin bridge to complicated thumb triplications with triphalangeal, deviating, and hypoplastic components. Radial polydactyly can be classified into one of 7 osseous presentations using the Wassel classification, with type IV (45%), type II (20%), and type VII (15%) occurring most frequently. When faced with a radial polydactyly case, hand surgeons specialised in congenital anomalies must weigh the preoperative functional potential and degree of hypoplasia of both thumbs in order to decide whether to resect one thumb and reconstruct the other (‘resection and reconstruction’), excise a central part of both thumbs and unite the lateral tissues into one thumb (‘the Bilhaut procedure’), transfer the better-developed distal tissues of one thumb onto the better-developed proximal tissues of the other (‘on-top plasty’), or discard both severely hypoplastic thumbs and pollicise the index finger. Mere excision of the hypoplastic thumb is rarely indicated since it often requires subsequent revision surgery. Even after being treated by experienced surgeons, about 15% of patients with polydactyly will need additional procedures to correct residual and/or new problems such as deviation from the longitudinal axis and joint instability. Nevertheless, radial polydactyly patients usually achieve unimpaired everyday hand function postoperatively.
Keywords: thumb duplication; Bilhaut procedure; radial polydactyly